Design and fabricating sequential control based automatic sweet potato stick machine - Jajang Jaenudin; Tedy Rahman; Edilla; Tianur (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Currently, one of the significant challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the food processing sector is enhancing both efficiency and effectiveness, particularly in the production of sweet potato sticks, commonly known as